POLITIK AGENDA SETTING DALAM LEGALISASI TANAMAN GANJA SEBAGAI USULAN REVISI PADA UU NARKOTIKA NO 35 TAHUN 2009 DI INDONESIA - Danny Bahar, Doddy Syamsul; Erawan, I Ketut Putra; Jayanthi Mertha, Anak Agung Sagung Mirah Mahaswari (Jurnal Nawala Politika, 2021)
The Narcotics Law in Indonesia is currently in a position to discuss the revised discourse, which in the process requires various institutional supports. In the process, there are various kinds of regulations that are needed to realize the revision of the law itself, one of which is the role of the executive and legislature in making and discussing the text of the law so that it is necessary to create a thorough integrity of the relevant agencies. Not only that, in the drafting or process of discussing laws, elements of society from various backgrounds have their own roles in the discussion of laws, as is the case in the RDP agenda or hearings held by the DPR RI for certain commissions.. Keywords: Agenda Setting, Legalization of Mariyuana, Revision of Narcotics Law